We might need a little anxiety: A finding of the students' problem-solving on fraction operation - Yuli Purwasih; Vita Istihapsari; Afit Istiandaru (International Journal on Education Insight, 2020)
One of the factors affecting the students' mathematical problem-solving ability is the mathematics anxiety. It was commonly believed that the higher anxiety a student feels, the lower performance the student does. This research aims to describe the students' problem-solving performance on fraction operation within three levels of mathematics anxiety - the high, the moderate, and the low anxiety. In this research, we selected six subjects by administering a questionnaire. The subjects - representing each of the anxiety levels - engaged in a problem-solving test on fraction operation and then being interviewed about their problem-solving process based on Polya framework. After a number of triangulations and discussions, we found that the students with high anxiety tended to ruin their problem-solving process due to somatic symptoms. We also found that the students with moderate anxiety developed a good care such that the process going well. Interestingly, the students with low anxiety did not carefully solve the problems and made some mistakes in calculation. A simple question might be addressed for future research. Does anxiety sometimes develop a good alert that makes the student careful about their problem-solving steps?